(untitled) (Current Horticulture, 2024)
With the changes in cropping system, climate and introduction of highly input-intensive high-yielding varieties/hybrids are the root cause for a shift in insect pest status in time and space, resulting in enhanced damage caused by them in the world. Many of them also act as vectors for several viral and mycoplasma diseases, aggravating the problem further. In India, yield loss due to major insect pests is varying from 30-40%. In addition to the regular pests, recently, many exotic and invasive insect pests have invaded in many parts of the countries. South American pin worm (Tuta absoluta Meyrick), solenopsis mealy bug (Phenacoccus solenopsis Tinsley) are few such insects. Similarly, mirid bugs (Nesidiocoris cruentatus (Ballard) and Metacanthus pulchellus Dallas), melon weevil [Acythopius curvovistris citrulli (Marshall)], white plume moth [Sphenarches caffer (Zeller)], cucumber moth (Diaphania indica) and moringa fruit borer (Noorda blitealis Walker), tortoise beetle (Cassida circumdata Herbst) are the insects which have come up in bigger way in current decade either by expanding their host horizon or increase their severity. Therefore, these emerging insect pests in vegetable ecosystem in current decade, their suitable control measures and some issues/challenges in their ecofriendly management are discussed.